Exome sequencing reveals variants in known and novel candidate genes for severe sperm motility disorders. Issue 9 (5th June 2021) - Oud, M S; Houston, B J; Volozonoka, L; Mastrorosa, F K; Holt, G S; Alobaidi, B K S; deVries, P F; Astuti, G; Ramos, L; Mclachlan, R I; O'Bryan, M K; Veltman, J A; et al.
Abstract: STUDY QUESTION: What are the causative genetic variants in patients with male infertility due to severe sperm motility disorders? SUMMARY ANSWER: We identified high confidence disease-causing variants in multiple genes previously associated with severe sperm motility disorders in 10 out of 21 patients (48%) and variants in novel candidate genes in seven additional patients (33%). WHAT IS KNOWN ALREADY: Severe sperm motility disorders are a form of male infertility characterised by immotile sperm often in combination with a spectrum of structural abnormalities of the sperm flagellum that do not affect viability. Currently, depending on the clinical sub-categorisation, up to 50% of causality in patients with severe sperm motility disorders can be explained by pathogenic variants in at least 22 genes. STUDY DESIGN, SIZE, DURATION: We performed exome sequencing in 21 patients with severe sperm motility disorders from two different clinics. PARTICIPANTS/MATERIALS, SETTING, METHOD: Two groups of infertile men, one from Argentina (n = 9) and one from Australia (n = 12), with clinically defined severe sperm motility disorders (motility <5%) and normal morphology values of 0–4%, were included. All patients in the Argentine cohort were diagnosed with DFS-MMAF, based on light and transmission electron microscopy. Sperm ultrastructural information was not available for the Australian cohort. Exome sequencing was performed in all 21 patients and variants with an allele frequency of <1% in the gnomAD population were prioritised and interpreted. MAIN RESULTS AND ROLE OF CHANCE: In 10 of 21 patients (48%), we identified pathogenic variants in known sperm assembly genes: CFAP43 (3 patients); CFAP44 (2 patients), CFAP58 (1 patient), QRICH2 (2 patients), DNAH1 (1 patient) and DNAH6 (1 patient). The diagnostic rate did not differ markedly between the Argentinian and the Australian cohort (55% and 42%, respectively). Furthermore, we identified patients with variants in the novel human candidate sperm motility genes: DNAH12, DRC1, MDC1, PACRG, SSPL2C and TPTE2 . One patient presented with variants in four candidate genes and it remains unclear which variants were responsible for the severe sperm motility defect in this patient. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: In this study, we described patients with either a homozygous or two heterozygous candidate pathogenic variants in genes linked to sperm motility disorders. Due to unavailability of parental DNA, we have not assessed the frequency of de novo or maternally inherited dominant variants and could not determine the parental origin of the mutations to establish in all cases that the mutations are present on both alleles. WIDER IMPLICATIONS OF THE FINDINGS: Our results confirm the likely causal role of variants in six known genes for sperm motility and we demonstrate that exome sequencing is an effective method to diagnose patients with severe sperm motility disorders (10/21 diagnosed; 48%). Furthermore, our analysis revealed six novel candidate genes for severe sperm motility disorders. Genome-wide sequencing of additional patient cohorts and re-analysis of exome data of currently unsolved cases may reveal additional variants in these novel candidate genes. STUDY FUNDING/COMPETING INTEREST(S): This project was supported in part by funding from the Australian National Health and Medical Research Council (APP1120356) to M.K.O.B., J.A.V. and R.I.M.L., The Netherlands Organisation for Scientific Research (918-15-667) to J.A.V., the Royal Society and Wolfson Foundation (WM160091) to J.A.V., as well as an Investigator Award in Science from the Wellcome Trust (209451) to J.A.V. and Grants from the National Research Council of Argentina (PIP 0900 and 4584) and ANPCyT (PICT 9591) to H.E.C. and a UUKi Rutherford Fund Fellowship awarded to B.J.H.